Recurrent Cholangiocarcinoma in Pregnancy: A Case Report - Francis, Antonia P.; Chang, Michelle; Dolin, Cara D.; Chervenak, Judith; Cardonick, Elyce (American Journal of Perinatology Reports, 2018)
Hepatobiliary malignancies during pregnancy are extremely rare and portend a poor prognosis. There are only seven published cases of cholangiocarcinoma in an obstetrical patient, all are cases of primary cholangiocarcinoma (1–7). Herein, we describe the first case of recurrent cholangiocarcinoma during pregnancy. The patient did not receive chemotherapy during pregnancy and required prolonged hospitalizations for nutritional and intensive medical support. She delivered preterm, at 30 2/7 weeks gestation, after developing pre-eclampsia with severe features. The infant was healthy, with no malformations, and currently exhibits no neurological or behavioral sequelae at 8months of age. We discuss themanagement considerations inherent to this complex clinical scenario including metastatic disease severity, ethical considerations, and palliative care treatment options.
Keywords: cancer; pregnancy; cholangiocarcinoma; hepatobiliary